Rising Threat of Carbapenem-Resistant Enterobacterales in Bangladesh: Challenges and Future Directions - Salam, Md. Abdus (Bangladesh Journal of Infectious Diseases, 2026)
Carbapenem-resistant Enterobacterales (CRE) represent a rapidly escalating threat in Bangladesh, posing significant challenges to public health within both hospital and community settings. Recent studies report alarmingly high CRE colonization rates of up to 37% among hospitalized patients, with community prevalence, albeit comparatively reduced, underscores the risk of extensive dissemination. The rise of CRE is driven by the proliferation of carbapenemase genes such as New Delhi metallo-β-lactamase (NDM), often facilitated by antibiotic misuse, inadequate infection control, and poor sanitation. Although surveillance and diagnostic capacities are evolving, their consistent deployment at the national scale remains limited. Current responses focus on infection prevention programs, antimicrobial stewardship, and public awareness efforts, yet these require greater coordination and investment in capacity building and research to address molecular trends and resistance profiles. Moving forward, Bangladesh faces an urgent need to enforce stronger regulatory frameworks, expand surveillance, and prioritize education and targeted interventions to contain CRE and safeguard the efficacy of available antibiotics. Bangladesh Journal of Infectious Diseases, December 2025;12(2):306-311